Role of IP-10 to Predict Clinical Progression and Response to IL-6 Blockade With Sarilumab in Early COVID-19 Pneumonia. A Subanalysis of the SARICOR Clinical Trial. (11th March 2023) - Trigo-Rodríguez, Marta; Cárcel, Sheila; Navas, Ana; Espíndola-Gómez, Reinaldo; Garrido-Gracia, José Carlos; Esteban Moreno, María Ángeles; León-López, Rafael; Pérez-Crespo, Pedro María Martínez; Alonso, Eduardo Aguilar; Vinuesa, David; Romero-Palacios, Alberto; Pérez-Camacho, Inés; et al.
Abstract: Background: The Clinical Trial of Sarilumab in Adults With COVID-19 (SARICOR) showed that patients with coronavirus disease 2019 (COVID-19) pneumonia and increased levels of interleukin (IL)-6 might benefit from blockade of the IL-6 pathway. However, the benefit from this intervention might not be uniform. In this subanalysis, we sought to determine if other immunoactivation markers, besides IL-6, could identify which subgroup of patients benefit most from this intervention. Methods: The SARICOR trial was a phase II, open-label, multicenter, controlled trial (July 2020–March 2021) in which patients were randomized to receive usual care (UC; control group), UC plus a single dose of sarilumab 200 mg (sarilumab-200 group), or UC plus a single dose of sarilumab 400 mg (sarilumab-400 group). Patients who had baseline serum samples for cytokine determination (IL-8, IL-10, monocyte chemoattractant protein–1, interferon-inducible protein [IP]-10) were included in this secondary analysis. Progression to acute respiratory distress syndrome (ARDS) according to cytokine levels and treatment received was evaluated. Results: One hundred one (88%) of 115 patients enrolled in the SARICOR trial had serum samples (control group: n = 33; sarilumab-200: n = 33; sarilumab-400: n = 35). Among all evaluated biomarkers, IP-10 showed the strongest association with treatment outcome. Patients with IP-10 ≥2500 pg/mL treated with sarilumab-400 had a lower probability of progression (13%) compared with the control group (58%; hazard ratio, 0.19; 95% CI, 0.04–0.90; P = .04). Conversely, patients with IP-10 <2500 pg/mL did not show these differences. Conclusions: IP-10 may predict progression to ARDS in patients with COVID-19 pneumonia and IL-6 levels >40 pg/mL. Importantly, IP-10 value <2500 pg/mL might discriminate those individuals who might not benefit from sarilumab therapy among those with high IL-6 levels.